Electroporation-mediated Delivery of Genes in Rodent Models of Lung Contusion - Machado-Aranda, David (Methods Mol Biol, 2014)
Several of the biological processes involved in the pathogenesis of acute lung injury and acute respiratory distress syndrome after lung contusion are regulated at a genetic and epigenetic level. Thus, strategies to manipulate gene expression in this context are highly desirable not only to elucidate the mechanisms involved but also to look for potential therapies. In the present chapter, we describe mouse and rat models of inducing blunt thoracic injury followed by electroporation-mediated gene delivery to the lung. Electroporation is a highly efficient and easily reproducible technique that allows circumvention of several of lung gene delivery challenges and safety issues present with other forms of lung gene therapy.